2015
DOI: 10.1021/la5048968
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Adsorption of Weak Acids on Graphite Using Amplitude Modulation–Frequency Modulation Atomic Force Microscopy

Abstract: Recent thermodynamics calculations and adsorption isotherms showed that the adsorption of a self-assembled layer (SAL) of ionized weak acids to carbon was attributed to the negatively charged hydrogen bonding (-CAHB), yet the direct visualization and characterization of this adsorption behavior have not been reported. Here, an amplitude modulation-frequency modulation atomic force microscopy (AM-FM AFM) technique was applied to discriminate the adsorption of decanoic acids (DA) on highly ordered pyrolytic grap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…103,104 Complexes between decanoic acid and −OH and −CO 2 H groups on functionalized highly ordered pyrolytic graphite that appear to form the CAHB have recently been imaged by atomic force microscopy. 104 The observed sorption obviously has contributions from hydrophobic effects, van der Waals, and specific interactions that may otherwise take place. 103 Ionizable compounds make up a large percentage of industrial pollutants, pesticides, personal care products, surfactants, pharmaceuticals, polyfluorinated compounds, and other compounds of emerging interest.…”
Section: Sorptive Activity Of Pcmmentioning
confidence: 99%
See 1 more Smart Citation
“…103,104 Complexes between decanoic acid and −OH and −CO 2 H groups on functionalized highly ordered pyrolytic graphite that appear to form the CAHB have recently been imaged by atomic force microscopy. 104 The observed sorption obviously has contributions from hydrophobic effects, van der Waals, and specific interactions that may otherwise take place. 103 Ionizable compounds make up a large percentage of industrial pollutants, pesticides, personal care products, surfactants, pharmaceuticals, polyfluorinated compounds, and other compounds of emerging interest.…”
Section: Sorptive Activity Of Pcmmentioning
confidence: 99%
“…By contrast, the CAHB has considerable covalent character ,,, and can be upward of 37 kJ/mol. Reactions and have been shown to contribute to adsorption of weak acids ranging in p K a from 4 to 7, including aliphatic and aromatic carboxylic acids, phenols, aryl sulfonamides, and heterocyclic amines, on chars, , partially oxidized CNTs, ,, and functionalized graphite. , Complexes between decanoic acid and −OH and −CO 2 H groups on functionalized highly ordered pyrolytic graphite that appear to form the CAHB have recently been imaged by atomic force microscopy . The observed sorption obviously has contributions from hydrophobic effects, van der Waals, and specific interactions that may otherwise take place .…”
Section: Sorptive Activity Of Pcmmentioning
confidence: 99%
“…Scanning probe microscopy (SPM), as a powerful characterization tool, has been successfully used to probe the surface topography, local mechanical property, and conductivity of the electrode materials at the nanoscale. Among them, bimodal atomic force microscopy (AFM) (amplitude modulation–frequency modulation, AM–FM) is a particular technique that is capable of mapping the surface topography and mechanical property of the materials simultaneously . Compared with nanoindentation, the significant advantage of the bimodal AFM is nondestructive measurement due to small forces of magnitude in the order of nano-Newtons between the tip and the surface, providing an opportunity to study the evolution of the materials in their native environment and state.…”
Section: Introductionmentioning
confidence: 99%
“…16−21 Among them, bimodal atomic force microscopy (AFM) (amplitude modulation−frequency modulation, AM−FM) is a particular technique that is capable of mapping the surface topography and mechanical property of the materials simultaneously. 22 Compared with nanoindentation, the significant advantage of the bimodal AFM is nondestructive measurement due to small forces of magnitude in the order of nano-Newtons between the tip and the surface, providing an opportunity to study the evolution of the materials in their native environment and state. Moreover, the bimodal AFM guarantees the constant sensitivity across the material surface even if the surface is inhomogeneous and more quantitative data is sought.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Hirayama et al 13 extended their method to include a hexadecane-based model lubricant that is more viscous than water. Moustafa et al 29 conducted a bimodal AFM study to visualize the lateral distribution of weakly adsorbed organic aggregates over graphite surfaces. A recent mapping study on a liquid ester lubricant with no modifier 30 reported the deposition of soft layers on a diamondlike carbon film following rubbing in a friction test, which was most likely a result of the tribochemical reactions of the lubricant.…”
Section: Resultsmentioning
confidence: 99%